2016
DOI: 10.1016/j.cap.2016.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of the epitaxial growth of Si films in Si heterojunction solar cells by the formation of ultra-thin oxide layers

Abstract: The epitaxial growth of silicon (Si) films during the catalytic chemical vapor deposition (Cat-CVD) of intrinsic amorphous Si (i-a-Si) passivation films on crystalline Si (c-Si) wafers is suppressed by the oxidation of c-Si surfaces simply by dipping the c-Si wafers in hydrogen peroxide (H 2 O 2 ). This oxidation treatment is also effective for (111)-oriented c-Si surfaces particularly at high a-Si deposition temperatures. The suppression of the epitaxial growth leads to the better effective minority carrier l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In other studies of conventional thermal oxides values of 10-30 % were observed[6]. Thus, formation of suboxides at the SiO 2 /Si interface turned out to be effectively suppressed (for TPO, RTO, WC-NAOS, PO) indicating a chemically abrupt interface.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In other studies of conventional thermal oxides values of 10-30 % were observed[6]. Thus, formation of suboxides at the SiO 2 /Si interface turned out to be effectively suppressed (for TPO, RTO, WC-NAOS, PO) indicating a chemically abrupt interface.…”
mentioning
confidence: 85%
“…Typical examples are passivated contacts in silicon solar cells [1,2], intermediate layers in metal-insulatorsemiconductor (MIS) solar cells [3], passivation of the amorphous/crystalline silicon (a-Si:H/c-Si) heterojunction [4][5][6], and barrier layer in silicon-based single and multi-junction quantum well solar cells [7,8]. Very recently, 25.1 % efficiency was achieved on a both sides-contacted Si solar cell featuring tunnel oxide passivated contacts [9].…”
Section: Introductionmentioning
confidence: 99%
“…[1,14,15] The growth condition of the i-layer has to be controlled carefully for preventing epitaxial growth at the a-Si:H/c-Si interface, which is generally detrimental for surface passivation. [16][17][18] To this end, interfacial layers such as porous (underdense) a-Si:H layers, [4,[19][20][21] a-Si:H alloys, including amorphous silicon oxides and carbides (a-SiO X :H [22,23] and a-SiC X :H [24] ), and very thin oxides [25,26] have been investigated. In addition, hydrogen dilution of SiH 4 plasma [18,27,28] has a significant impact on the surface passivation.…”
mentioning
confidence: 99%
“…The oxidation of silicon surfaces shows promising properties that have made them the focus of many research groups , which have sought to employ various silicon oxidation techniques in the fabrication of semiconductor devices. These oxidized layers can be used as a key ingredient in creating many electronic devices such as, passivated contacts in silicon solar cells [1,2], multi-junction quantum well solar cells [7,8], and barrier layer in silicon-based single and passivation of the amorphous/crystalline Si (a-Si:H/c-Si) heterojunction [4][5][6], etc.…”
Section: Introductionmentioning
confidence: 99%